Applications of 1, 3, 5-trimethoxybenzene as a derivatizing agent for quantifying free chlorine, free bromine, bromamines, and bromide in aqueous systems. Issue 43 (1st October 2019) - Dias, Ryan P.; Schammel, Marella H.; Reber, Keith P.; Sivey, John D.
Abstract : Free chlorine and free bromine ( e.g., HOCl and HOBr) are employed as disinfectants in a variety of aqueous systems, including drinking water, wastewater, ballast water, recreational waters, and cleaning products. Abstract : Free chlorine and free bromine ( e.g., HOCl and HOBr) are employed as disinfectants in a variety of aqueous systems, including drinking water, wastewater, ballast water, recreational waters, and cleaning products. Yet, the most widely used methods for quantifying free halogens, including those employing N, N -diethyl- p -phenylenediamine (DPD), cannot distinguish between HOCl and HOBr. Herein, we report methods for selectively quantifying free halogens in a variety of aqueous systems using 1, 3, 5-trimethoxybenzene (TMB). At near-neutral pH, TMB reacted on the order of seconds with HOCl, HOBr, and inorganic bromamines to yield halogenated products that were readily quantified by liquid chromatography or, following liquid–liquid extraction, gas chromatography-mass spectrometry (GC-MS). The chlorinated and brominated products of TMB were stable, and their molar concentrations were used to calculate the original concentrations of HOCl (method quantitation limit (MQL) by GC-MS = 15 nmol L −1 = 1.1 μg L −1 as Cl2 ) and HOBr (MQL by GC-MS = 30 nmol L −1 = 2 μg L −1 as Cl2 ), respectively. Moreover, TMB derivatization was efficacious for quantifying active halogenating agents in drinking water, pool water, chlorinated surface waters, and simulated spa waters treated with 1-bromo-3-chloro-5, 5-dimethylhydantoin. TMB was also used to quantify bromide as a trace impurity in 20 nominally bromide-free reagents (following oxidation of bromide by HOCl to HOBr). Several possible interferents were tested, and iodide was identified as impeding accurate quantitation of HOCl and HOBr. Overall, compared to the DPD method, TMB can provide lower MQLs, larger linear ranges, and selectivity between HOCl and HOBr.